Unveiling pathogenesis of pelvic organ prolapse through transcriptomic and bioinformatic analyses in uterosacral ligament tissues of postmenopausal women - Rui, BingJie; Rui, GuangHai; Yang, YanFeng (Frontiers in Genetics, 2025)
BackgroundPelvic organ prolapse (POP) is a common gynecological disorder arising from an imbalance in the synthesis and degradation of pelvic supportive tissues. Alterations in key molecules and genetic mutations affecting extracellular matrix (ECM) remodeling have been implicated in its development. This study aimed to profile coding and noncoding RNAs (ncRNAs) in uterosacral ligament tissues of postmenopausal women to elucidate POP’s molecular mechanisms.MethodsWe enrolled five POP patients and three normal controls. Uterosacral ligament tissue samples were collected and analyzed using high-throughput transcriptome sequencing to profile messenger RNAs (mRNAs), micro RNAs (miRNAs), circular RNAs (circRNAs), and long noncoding RNAs (lncRNAs). Differential expression was determined using the criteria of |log2 (fold change)|>1 and an adjusted p-value (padj) < 0.05. Bioinformatics analyses, including Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment, were performed to assess the functional roles of the differentially expressed genes. Competing endogenous RNA (ceRNA) networks were constructed to explore interactions among lncRNAs, miRNAs, and mRNAs. Real-time quantitative polymerase chain reaction (qPCR) validated selected targets.ResultsWe identified 60 mRNAs, 146 miRNAs, 29 lncRNAs, and 176 circRNAs with significant differential expression in POP tissues. Functional enrichment analyses revealed that these transcripts are primarily involved in cellular senescence, inflammation, ECM regulation, and cytoskeletal organization. Several signaling pathways were enriched, including those mediated by mitogen-activated protein kinase (MAPK), Extracellular Signal-Regulated Kinase 1/2(Erk1/2), Ras-related proteins (Rap1), Forkhead Box O (FOXO), and other oncogene homologs. Analysis of ceRNA networks uncovered interactions among lncRNAs, miRNAs, and mRNAs. Notably, lncRNA FLJ20021 was significantly downregulated in POP tissues and correlated with altered expression of collagenⅢ (COL III), CollagenⅠ (COL I), and Matrix Metalloproteinase-9 (MMP9).ConclusionOur findings demonstrate significant alterations in both coding and ncRNAs expression in POP tissues, suggesting that dysregulation of multiple pathways contributes to its pathogenesis. In particular, ECM remodeling and reduced FLJ20021 expression may play key roles in tissue degeneration, offering potential targets for future therapeutic intervention.